Salisiah Adat: Perkawinan Lintas Adat antara Pariaman dan Luhak 50 Kota dalam tinjauan Hukum Islam - Juszal Mita; Dahyul Daipon (Journal of Islamic Law and Wisdom, 2025)
The Inter-traditional marriages have long been occurring in Minangkabau, such as in Pariaman and Luhak 50 Kota. In Pariaman it is known as the bajampuik system, that is the prospective husband asks for a certain amount of money from the prospective wife who comes from another tradition. Meanwhile in Luhak 50 Koto it is known as the maisi sasuduik system or the prospective wife's party asks the prospective husband's party to provide all the contents of the bridal chamber. This system certainly needs to be reviewed for its suitability with Islamic Law because it sometimes escapes the attention of researchers. Through qualitative research with data sources of observation, interviews and documentation, it is known that the Inter-customary marriage as mentioned is following Indonesian law. In addition, inter-customary marriage in Pariaman and Luhak does not violate Islamic law or 'Urf as agreed by experts. However, the decision to carry out or not the marriage is in the hands of each customary ruler